2015
DOI: 10.1371/journal.pntd.0003863
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Burkholderia mallei tonB Mutant and Its Potential as a Backbone Strain for Vaccine Development

Abstract: BackgroundIn this study, a Burkholderia mallei tonB mutant (TMM001) deficient in iron acquisition was constructed, characterized, and evaluated for its protective properties in acute inhalational infection models of murine glanders and melioidosis.Methodology/Principal FindingsCompared to the wild-type, TMM001 exhibits slower growth kinetics, siderophore hyper-secretion and the inability to utilize heme-containing proteins as iron sources. A series of animal challenge studies showed an inverse correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 57 publications
(74 reference statements)
5
44
2
Order By: Relevance
“…7A). These findings are consistent with previous reports indicating that high Th1 bias antibody titers afford superior protection (109,(130)(131)(132)(133). Our data also underscore a protective role for antibodies of the IgG subclass ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…7A). These findings are consistent with previous reports indicating that high Th1 bias antibody titers afford superior protection (109,(130)(131)(132)(133). Our data also underscore a protective role for antibodies of the IgG subclass ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the incorporation of antibody-inducing proteins is important when designing a subunit vaccine against Burkholderia. Nevertheless, it is currently understood that balanced cellular and humoral immune responses will be required for vaccine-induced protective immunity against B. pseudomallei and B. mallei (29,(36)(37)(38). Interestingly, in the present study, there does not appear to be a direct correlation between antibody titers (anti-LPS or antiprotein) and protection.…”
Section: Use Of Novel Burkholderia Antigens For Nanovaccinescontrasting
confidence: 61%
“…challenged with 1.5 ϫ 10 4 CFU of B. mallei strain lux (CSM001) had survival rates of 100% and 75%, respectively. Necropsy and organ CFU enumeration showed that all mice had splenomegaly and splenic abscesses due to TMM001 colonization (16). This study was significant because it revealed the first attenuated strain to provide 100% and 75% survival against B. mallei and B. pseudomallei challenge, respectively.…”
mentioning
confidence: 77%
“…Live attenuated vaccines, the use of which is regarded as the most viable strategy against B. mallei, have been tested with some success (14)(15)(16)(17). Recently, our laboratory evaluated an iron acquisition-deficient B. mallei ⌬tonB (TMM001) strain for use as a live attenuated vaccine in acute inhalational glanders and melioidosis (B. pseudomallei) murine models.…”
mentioning
confidence: 99%